Certificate of Accreditation for Programme Doctor of philosophy - Universiti Malaysia Sarawak (Universiti Malaysia Sarawak (UNIMAS), 2013)
Certificate of Accreditation for Programme Doctor of philosophy has attained the quality assurance standards set by the agency and is in compliance with the Malaysian qualifications framework Level 8. Date of Accreditation : 11/09/2013